Pentingnya Konten Media Sosial Sekolah Kristen di Surabaya Terhadap Brand Awareness - Suwito, Jennifer Putri; Suhartono, Ani Wijayanti; Basuki, Rebecca Milka Natalia (Fakultas Desain Universitas Komputer Indonesia, 2024)
This analysis aims to identify how Christian schools use social media to enhance their brand awareness. The primary focus is on evaluating the types of content, posting frequency, and user engagement levels, as well as their impact on brand awareness. Data is collected from several Christian schools and their social media content is analyzed over a specified period. It is hoped that the results of this analysis will provide valuable insights into effective strategies that educational institutions can apply to leverage social media for enhancing brand awareness.